Russian hybrid warfare: A study of disinformation - Flemming Splidsboel Hansen (Danish Institute for International Studies (DIIS), 2017)
The basic tenet of the Russian disinformation strategy is the claim that all news is constructed and therefore contested. In the best postmodern tradition they claim there is no 'objective news' - only different, rivalling interpretations which purport to show different aspects of what may be called 'reality'. And what the Russian media outlets present are merely possible explanations which serve as alternatives to the stories offered by Western media. It is a strategy which is both cunning and elegant as it preys on the enlightenment tradition and on the vulnerabilities of liberal democratic media. The Russian authorities seem to believe that (dis-) information campaigns hold great prospects. In a 2017 article, the Russian Chief of Staff informed the public about the Russian military thinking on the topic of 'war' and on the role of the non-military or "non-kinetic" in this. It seems premature to conclude that this thinking sees the possibility of war as an exclusively non-kinetic activity - this at least was not announced in the article - but the development points strongly in this direction and we should therefore expect to see an increased Russian focus on (dis-) information campaigns designed to bring well-defined outcomes. There will not be any easy or fix-it-all solutions to this development. Rather, liberal democracies, especially vulnerable as a result of their free media culture, should prepare themselves for a long-term commitment to countering disinformation and to building up cognitive resilience to ensure that the former has minimal effect.
Keywords: 300